Achieving the ASEAN Economic Community 2015: Challenges for the Philippines - Josef T. Yap; Fatima del Prado; Jenny D. Balboa (Philippine Institute for Development Studies (PIDS), 2010)
ASEAN member countries are moving toward achieving the ASEAN Economic Community (AEC) with the timeline set at 2015. It is therefore important for policymakers in the region to sustain the momentum - or perhaps even accelerate the pace - toward establishing the AEC. Policy measures are being implemented based on the AEC Blueprint agreed upon in 2007. However, progress among the ASEAN member countries in meeting their commitments has been uneven. This paper reviews the progress of the Philippines in meeting its commitments on the AEC and comparing it with achievements of other ASEAN countries. The paper also discusses some of the problems and constraints that may prevent the Philippines from benefiting from the AEC.
Keywords: 330; ASEAN; regional integration; Philippines; ASEAN Economic Community (AEC); Regionale Wirtschaftsintegration; ASEAN-Staaten; Handelsliberalisierung; Wirtschaftliche Anpassung; Philippinen